Efek Faktor Moderasi Gender pada Relasi Financial Literacy dan Financial Ignorance terhadap Perilaku Keuangan - Sari, Maya; Nurhayati, Netti Siska; Yuliawati, Tia (Image : Jurnal Riset Manajemen, 2023)
Financial well-being can be achieved through good financial behavior in the short and long term. Within the household group, financial behavior was associated with financial well-being, such as paying bills on time, saving, and investing. Financial literacy is one of the factors that form good financial behavior, on the other hand, financial ignorance leads to bad financial behavior. This study aims to examine the effect of gender moderation on the relationship between financial literacy and financial ignorance on financial behavior in household workers in Kota Bandung, Kabupaten Bandung and Kabupaten Bandung Barat. Primary data was taken through the distribution of google form questionnaires and collected as many as 75 samples. Data were analyzed using Moderated Regression Analysis (MRA). The results show that gender acts as a moderator in the relationship between financial literacy and financial ignorance on financial behavior. The partial test shows that an increase in financial literacy will have an impact on increasing positive financial behavior, on the contrary, an increase in financial ignorance will have an impact on decreasing positive financial behavior among respondents. The results of this study can be continued or developed by the next researcher, by adding several other moderating variables, such as class position, income, ethnicity, and others.